Characterization of MeWO4 (Me = Ba, Sr and Ca) nanocrystallines prepared by sonochemical method - Thongtem T. (2014)
Metal tungstates (MeWO4, Me = Ba, Sr and Ca) were successfully prepared using the corresponding Me(NO3)2·2H2O and Na2WO4·2H2O in ethylene glycol by the 5 h sonochemical process. The tungstate phases with scheelite structure were detected with X-ray diffraction (XRD) and selected area electron diffraction (SAED). Their calculated lattice parameters are in accord with those of the JCPDS cards. Transmission electron microscopy (TEM) revealed the presence of nanoparticles composing the products. Their average sizes are 42.0 ± 10.4, 18.5 ± 5.1 and 13.1 ± 3.3 nm for Me = Ba, Sr and Ca, respectively. Interplanar spaces of the crystals were also characterized with high-resolution TEM (HRTEM). Their crystallographic planes are aligned in systematic array. Six different vibration wavenumbers were detected using Raman spectrometer and are specified as ν1(Ag), ν3(Bg), ν3(Eg), ν4(Bg), ν2(Ag) and free rotation. Fourier transform infrared (FTIR) spectra provided the evidence of scheelite structure with W-O anti-symmetric stretching vibration of [WO4]2- tetrahedrons at 786-883 cm-1. Photoluminescence emission of the products was detected over the range of 384-416 nm. © 2008 Elsevier B.V. All rights reserved.